The impact of driving versus undistracted listening on podcast knowledge acquisition and retention using a driving simulator: A randomized, cross-over trial - Yasaman Jabbari; Michael Gottlieb; Martin von Mohrenschildt; Mark Lee; Kristen Arnold; Judith M. Shedden; Jonathan Sherbino (PLoS ONE, 2025)
Introduction Research on listening to podcasts while driving suggested no significant difference compared to undistracted listening. However, these studies were conducted in non-controlled driving environments, limiting the evaluation of the environment’s impact. This study aimed to compare knowledge acquisition and retention among resident physicians and undergraduate students while listening to medical education podcasts in a controlled, simulator-based, driving environment versus an undistracted listening condition. Methods A randomized, crossover trial involved 19 residents and 22 undergraduate students from McMaster university and McMaster hospital. Participants listened to podcasts while driving in an immersive, high-fidelity motion simulator that mimics different driving environments: a high-distraction city environment and a low-distraction country environment. In the undistracted listening condition, participants listened to podcasts while being seated at a desk. Immediate and delayed recall tests after a month were administered, and data were analyzed using a 2x2 mixed ANOVA. Results There were no significant differences in knowledge acquisition (e.g., accuracy) between the undistracted, city driving, and country driving conditions (p > 0.05, η2 = 0.011). However, the country driving condition demonstrated slightly higher accuracy compared to the city driving condition in the immediate assessment condition (p < 0.05, η2 = 0.018). Medical expertise level (i.e., resident vs student) did not affect knowledge acquisition across different listening conditions (p > 0.05, η2 = 0.007). Conclusion In a simulated environment, knowledge acquisition from a podcast is not compromised by the attention needed for driving a vehicle. The two distraction levels used in this experiment showed no significant interference with knowledge acquisition. This holds true regardless of participants’ medical expertise. This study highlights the potential of incorporating podcasts into daily commuting to support ongoing education without requiring dedicated study time, enhancing both flexibility and efficiency in professional development.